Pengembangan Media Pembelajaran Ensiklopedia IPA Berbasis Pendekatan Contextual Teaching & Learning (CTL) pada Materi Energi dan Perubahannya untuk Siswa Kelas III Sekolah Dasar - Rieska Hadisumarno Putri; Candra Puspita Rini; Ferry Perdiansyah (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
This research is a development research that aims to produce learning media products in the form of a science encyclopedia book based on Contextual Teaching & Learning (CTL) on energy material and its changes for third grade elementary school students and to determine the quality of learning media based on aspects of validity and feasibility aspects. This research refers to the 4D model (Define, Design, Development, Disseminate). The population subjects in this study were third grade students at SD Negeri Sukasari 7, Tangerang City. The instruments used to measure the quality of the learning media developed in this study were the validity aspect assessment sheet by media experts and material experts, the feasibility aspect assessment sheet by the classroom teacher, and student response questionnaires. an average score of 3.95 which indicates